Pengaruh Store Atmosphere dan Kualitas Pelayanan Terhadap Kepuasan Konsumen KFC Purus Veteran Kota Padang - Tiara Maharani; Nidia Wulansari (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
The findings of problems related to store atmosphere and service quality on customer satisfaction are the impetus for this research. This study aims to examine how customer satisfaction at KFC Purus Veteran Padang City is influenced by store atmosphere and service quality. Quantitative research is the methodology used. Primary data is the type of data used in this study. The participants in this study were consumers of KFC Purus Veteran Padang City. This study involved a sample size of 97 consumers, who were selected through the non-probability sampling method. Data collection was carried out using a Likert scale questionnaire that had been tested for validity and reliability. The data were analyzed using SPSS 23.00 software. The findings show that the store atmosphere received a high rating of 4.08% which indicates a positive perception among consumers. In addition, consumer satisfaction was rated at 3.68% and service quality at 3.49%, both of which fell into the satisfactory category. The results also show a significant effect of store atmosphere (X1) and service quality (X2) on customer satisfaction (Y). The Adjusted R Square value of 0.187 indicates that these variables explain 18.7% of the variance in customer satisfaction, while the remaining 81.3% is influenced by other factors not examined in the study. Translated with DeepL.com (free version). Next, the F value is calculated with sig. 0.000 < 0.05 is 12,070.